Study of Predictive factors of public health based on job satisfaction in employees of Rasht city Health Service Centers - Farideh Kamali Dehkordi; Shahrokh Maghsoudi; Abdolhossein Emami Sigaroudi; Ehsan Kazemnejad Leili (Journal of Holistic Nursing and Midwifery)
Abstract